Case Study : Bakeology Mart Company / Nurul Farahain Junaidi - Junaidi, Nurul Farahain (2020)
Case study report has been done to give an idea on how to apply technology solution in real life based on what students learned about technology entrepreneurship. To complete this task, we interviewed the owner of the Bakeology Mart company which is one of the bakery ingredients shop in Terengganu. For reader information, this company has many category products that we will group them into three parts which are bakery ingredients, bakery tools and frozen products. Therefore, this company were chosen since we are interested to develop a product for storage of bakery tools. Before the actual research to be done, we had done a few researches on article related to the storage for bakery tools since we only focus on the storage product. This is important so that we are able to understand the experience of people using current product. We can analyse the problem they had when they use the product. From that, we can design our innovation product to solve their problem. After that, we gather the general information of this company through interview and observation methods. The information of the company background, product, services and technologies use in the company were collected. Besides, all the strategies used by the company to promote their products and achievement of this company are collected using above methods. We were able to identify the company’s strengths, weaknesses, opportunities and threats through analysis of SWOT